PEMBUATAN BRACKET FINISH PANEL MOUNTING D74 MENGGUNAKAN MESIN PRESS STAMPING PUX 100 - Prasetya, Divara; Jannati, Eidelweis Dewi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
This practical work report describes the process of making part bracket finish panel mounting type d74 using PUX 100 stamping press machine and the operating procedures of stamping press machine at PT Persada Selaras Indoensia. The aim is to know directly during the process of making part bracket finish panel mounting type d74, and to know how to operate the stamping press machine. The manufacturing process of bracket finish panel mounting type d74 consists of several stages starting from material checking using SPC440, product design checking, Stamping Press process with four stages of production process (blanking, forming, bending, & Pierching). In addition, this report discusses how to operate the stamping press starting from the machine inspection stage to the stamping press machine setting. Through this practical work report, it is hoped that readers can gain insight into the process of making bracket finish panel mounting type d74 parts and the company's contribution in maintaining product quality. Keywords : Stamping Press, SPC440, Production Process